Approaches to quantifying carbon emissions from degradation in pan‐tropic forests—Implications for effective REDD monitoring. (15th July 2019) - Lu, Heli; Liu, Guifang; Zhang, Chuanrong; Okuda, Toshinori
Abstract: Special attention is needed to quantify emissions from human‐induced degradation in forest lands because these data are more uncertain and less comprehensive than deforestation data in target countries in the United Nations Reducing Emissions from Deforestation and Forest Degradation (REDD) programme. This study illustrates a Residual Trends (RESTREND) technique with a new baseline that isolates the human influence from natural climatic fluctuations to estimate emissions from forest degradation in countries across the tropics. Based on the recommended Intergovernmental Panel on Climate Change methodology and framework, we found a pattern of high carbon density of 183 t C/ha in degraded areas, which was on average 1.5 times that of deforestation areas. Further analysis revealed that the initial value of carbon stock in degraded areas was about 5.45 Pg C during 2002–2012. We found that 17% of countries displayed values more than 100% of those from deforestation under the low degradation emission scenario, whereas 23% of countries displayed values less than 10% under the high degradation emission scenario. Thus, at a national level, with such an approach REDD could be further optimized and REDD targets could be achieved in an effective way.